Cobalt-Protoporphyrin Improves Heart Function by Blunting Oxidative Stress and Restoring NO Synthase Equilibrium in an Animal Model of Experimental Diabetes - Cao, Jian; Vecoli, Cecilia; Neglia, Danilo; Tavazzi, Barbara; Lazzarino, Giuseppe; Novelli, Michela; Masiello, Pellegrino; Paolocci, Nazareno; Puri, Nitin; L'Abbate, Antonio; Abraham, Nader G. (Frontiers in Physiology, 2012)
Myocardial dysfunction and coronary macro/microvascular alterations are the hallmarks of diabetic cardiomyopathy and are ascribed to increased oxidative stress and altered nitric oxide synthase (NOS) activity. We hypothesize that pre-treatment by cobalt-protoporphyrin IX (CoPP) ameliorates both myocardial function and coronary circulation in streptozotocin (STZ)-induced diabetic rats. Isolated hearts from diabetic rats in Langendorff configuration displayed lower left ventricular function and higher coronary resistance (CR) compared to hearts from control animals. CoPP treatment of diabetic animals (0.3 mg/100 g body weight i.p., once a week for 3 weeks) significantly increased all the contractile/relaxation indexes (p < 0.01), while decreasing CR (p < 0.01). CoPP enhanced HO-1 protein levels and reduced oxidative stress in diabetic animals, as indicated by the significant (p < 0.05) decrease in heart % GSSG, O2− and malondialdehyde (MDA) levels. CoPP increased adiponectin levels and phosphorylation of AKT and AMPK and reversed the eNOS/iNOS expression imbalance observed in the untreated diabetic heart. Furthermore, after CoPP treatment, a rise in malonyl-CoA as well as a decrease in acetyl-CoA was observed in diabetic hearts. In this experimental model of diabetic cardiomyopathy, CoPP treatment improved both cardiac function and coronary flow by blunting oxidative stress, restoring eNOS/iNOS expression balance and increasing HO-1 levels, thereby favoring improvement in both endothelial function and insulin sensitivity.